Work and Identity Contemporary Perspectives on Workplace Diversity (Palgrave Explorations in Workplace Stigma,, 2018)
This edited volume highlights relevant issues and solutions for diversity groups within the workplace. It explores issues of identity as they relate to attributes of gender, age, migrant labor, disability, and power in social spaces. Identity is rarely well-defined in many social spaces, and understandings that define belonging are often developed through the normative expectations of others. Having an evidence-based approach in addressing these relevant issues, this book will appeal to academics and practitioners alike looking for practical and theoretical solutions to improving the situations of these groups in paid employment.